Personal attribute judgments - Karapanos, Evangelos (My University, 2013)
Traditional approaches to measuring users' responses to artifacts lie in the a-priori definition of the measures by the researchers. This chapter highlights the limitations of such approaches that employ standardized psychometric scales and introduces personal attributes judgments. It introduces attribute elicitation techniques and in particular, the Repertory Grid Technique (RGT). It argues that the true value of RGT is in quantifying rich qualitative insights and highlights the limitations of relevant statistical techniques that are typically employed in the analysis of repertory grid data. An initial Multi-Dimensional Scaling (MDS) procedure that aims at identifying diverse views in Repertory Grid data is proposed. The procedure identifies distinct user groups in a sample population and derives a two-dimensional view for each respective user group. The technique is presented through a case study where users' views on a set of product concepts were contrasted to the ones of designers. The technique revealed differences not only between users and designers but also between designers of different professional background and role in the design team.
Keywords: Latent Construct; Technology Acceptance Model; Perceptual Space; Repertory Grid; Diverse View